Analisa Keausan Elektroda Electrical Discharge Machining Menggunakan Metoda Response Surface Methodology - Eko Yudo; Husman Husman (Politeknik Manufaktur Negeri Bangka Belitung, 2018)
The current electrical dish machine machining (EDM) machine in the field of manufacturing has developed along with conventional machines such as Lathes, Milling Machines, and Grinding Machines as the leading technology. EDM is known for its ability to make complex shapes on very hard metals. EDM machines are widely used in the manufacture of dies, cutting tools, and molds that cannot be done with the cutting process. Therefore the level of electrode wear in the EDM process must be as efficient as possible. The research was conducted to determine the exact EDM process parameter setting values. Variable parameters are current, on time, off time. To optimize the response of this study using the Response Surface Methodology (RSM) method. High electrode wear is obtained in testing with parameters used Ton (300 ?s), Toff (15 ?s) and Current (20 A), and the smallest wear value is obtained in the test with the parameters used Ton (100 ?s), Toff (15 ?s) and Current (10 A).